2005
DOI: 10.1902/jop.2005.76.12.2299
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Gingival Fibromatosis: Report of a Five‐Generation Family Using Cellular Proliferation Analysis

Abstract: Our data demonstrated that, in the studied family, HGF is transmitted by an autosomal dominant pattern with incomplete disease penetrance, and although the gingival enlargement resulted from an excessive accumulation of collagen fibers, HGF is characterized by an increase in the proliferation rate of epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
(33 reference statements)
2
32
0
2
Order By: Relevance
“…Previous studies indicated increased proliferation rates for epithelial cells and fibroblasts in HGF gingiva. Immunohistochemical assays for epidermal growth factors, epidermal growth factor receptor, proliferating cell nuclear antigen, and pKi-67 generally reported increased epithelial cell proliferation in HGF tissue (Araujo et al, 2003;Saygun et al, 2003;Almeida et al, 2005;Martelli-Junior et al, 2005). Increased fibroblast proliferation has also been reported with 5-bromo-2-deoxyuridine incorporation into DNA (Tipton et al, 1997(Tipton et al, , 2004Almeida et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies indicated increased proliferation rates for epithelial cells and fibroblasts in HGF gingiva. Immunohistochemical assays for epidermal growth factors, epidermal growth factor receptor, proliferating cell nuclear antigen, and pKi-67 generally reported increased epithelial cell proliferation in HGF tissue (Araujo et al, 2003;Saygun et al, 2003;Almeida et al, 2005;Martelli-Junior et al, 2005). Increased fibroblast proliferation has also been reported with 5-bromo-2-deoxyuridine incorporation into DNA (Tipton et al, 1997(Tipton et al, , 2004Almeida et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Whether the increased gingiva reflects increased cell numbers, extracellular collagen, or other extracellular constituents is not always clear, and the underlying mechanism is unknown. Reported histological, morphological, and cellular characteristics of HGF gingival tissues differ (Johnson et al, 1986;Shirasuna et al, 1988;Hou, 1993;Barros et al, 2001;Araujo et al, 2003;Saygun et al, 2003;Tipton et al, 2004;Almeida et al, 2005;Gagliano et al, 2005;Martelli-Junior et al, 2005). Genotype-phenotype correlations are problematic, because it is unknown if reported differences between individuals with HGF are due to variable expression of a common gene mutation, allelic mutations, non-allelic mutations, or methodological differences (Hart et al, 2000;Xiao et al, 2000Xiao et al, , 2001Tipton et al, 2004;Ye et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…5 HGF as an isolated feature is believed to be expressed as an autosomal dominant trait. 9 According to the genetic history of the present case, autosomal-dominant inheritance is a feasible diagnosis because family members of both sexes were affected, and the condition was present in two successive generations (mother and two sons); however, there was no history of consanguinity in the family.…”
Section: Discussionmentioning
confidence: 78%
“…It may manifest as an autosomaldominant and autosomal-recessive mode of inheritance [77,78]. Consanguinity has been observed in the recessive mode of familial gingival ibromatosis [79,80].…”
Section: Genetic Disorders With Periodontal Manifestations and Consanmentioning
confidence: 99%